PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS AKTIVITAS KONTEKSTUAL DI MI ALAM ALFA KIDS PATI - Choir, Abu (QUALITY, 2019)
This study aims to find and describe the learning process of Islamic Religious Education (PAI) based on contextual activities carried out at MI Alam Alfa Kids Pati. This study uses a type of descriptive qualitative research with a participatory approach. Data collection techniques using in-depth interviews, participatory observation, and document review. While data analysis used an interactive analysis model including data reduction, data delivery, and conclusion drawing. Based on the results and discussion of the study that PAI learning based on contextual activity is the learning of PAI contextualist reconstructive, namely the creative effort in PAI learning to bring it closer to real life, so that PAI becomes applicable and implementative in accordance with life's demands. To achieve this, an understanding of the following matters is needed: 1) Understanding the meaning of PAI-based activities that are reconstructive contextualists; 2) The ability to choose the types of activities that are reconstructive contextualists; 3) The process of recycling a reconstructive contextual education process. Keywords: Learning, PAI, Contextual